2014
DOI: 10.4184/asj.2014.8.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Pedicle Screw Fixation and Monosegmental Fusion in Patients with Fresh Thoracolumbar Fractures

Abstract: Study DesignProspective clinical study.PurposeThe present prospective study aims to evaluate the clinical, radiological, and functional and quality of life outcomes in patients with fresh thoracolumbar fractures managed by posterior instrumentation of the spine, using pedicle screw fixation and monosegmental fusion.Overview of LiteratureThe goals of treatment in thoracolumbar fractures are restoring vertebral column stability and obtaining spinal canal decompression, leading to early mobilization of the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Mean (±SD) time interval between injury and surgery was 13.6 ± 10 days (range 5 -30 days) in current study. Singh et al showed mean time interval between injury and surgery was 13.1 days (range 1 -31 days), which was accorded to this study [9].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Mean (±SD) time interval between injury and surgery was 13.6 ± 10 days (range 5 -30 days) in current study. Singh et al showed mean time interval between injury and surgery was 13.1 days (range 1 -31 days), which was accorded to this study [9].…”
Section: Discussionsupporting
confidence: 80%
“…But several authors reported that a long posterior stabilization is frequent used treatment modality [8] [9] [10]. However, posterior approach is less extensive, and most spine surgeons advocate posterior fusion as the treatment of choice for unstable thoracolumbar injuries [9]. Posterio-lateral fusion is considered as the gold standard in the treatment of thoracolumbar burst ftacture [10].…”
Section: Introductionmentioning
confidence: 99%
“…Preserving as many motion segments as possible by limiting the number of fused segments minimizes alteration of spinal biomechanics and the risk of early degeneration of adjacent segments, and therefore, constitutes a fundamental principle of spinal surgery. Following this principle, several studies [ 22 26 ] reported favorable outcome after monosegmental posterior fixation of selected thoracolumbar fractures. However, studies on monosegmental anterior column reconstruction are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…By selective fusion of superior intervertebral articular process, the inferior distal and proximal adjacent segments in the selective fusion group regained more motion after instrumentation removal. The selectively fused scheme restored the spine and alleviated the adjacent vertebral degeneration [21].…”
Section: Discussionmentioning
confidence: 99%